A SURVEY ON INTERNET OF THINGS BASED SMART BIN - Misimi Jonuzi, Verda; Mishkovski, Igor; CHorbev, Ivan (My University, 2023)
The conventional method of waste management has proven to be quite expensive and time-consuming, and the sorting of waste still is a challenge in traditional systems due to the lack of a habit of waste segregation by category. With the advent of IoT and IA technology, however, the traditional waste management approach can be replaced by the implementation of smart sensors for real-time monitoring and waste assessment, presenting an intelligent waste management system that saves both time and money. The main goal of this study is to develop a smart waste bin, equipped with sensors and actuators, to enable the proper allocation of waste for citizens' benefit and environmental cleanliness. The ultrasonic sensors for filling level, sensors for user identification, servo motor for lid opening, LCD display for fill level notification, motion detection sensor for identifying user departure and lid closure, camera for capturing garbage type images, and GPS sensor for basket location notification will all be connected to an Arduino UNO and a LoRaWAN network for communication between nodes (baskets) and database servers for system processing and monitoring.
Keywords: Internet of Things, Smart Waste, Smart Bin